2017
DOI: 10.5005/jp-journals-10024-1981
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Pubertal Growth Period using the Open Apices of the Lower Teeth

Abstract: Aim:The purpose of this study was to evaluate whether the open apex measurements of the lower teeth can be used for prediction of the pubertal growth spurt. Materials and methods:The study group consisted of 150 males and 142 females ranging in age from 10 to 16 years. A total of 292 panoramic and 292 hand-wrist radiographs were obtained and analyzed. The skeletal maturity was determined according to the skeletal maturity indicators (SMIs) developed by Fishman. The open apices measurements of the left lower te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
1
Order By: Relevance
“…This result was similar to Chertkow's findings [ 27 ]. Contrary to our results, two studies [ 38 , 39 ] found that the correlation has no statistically significant gender differences. These studies [ 38 , 39 ] used the open apices approach described by Cameriere et al [ 40 ], which is different from Demirjian et al's [ 41 ] method used in the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…This result was similar to Chertkow's findings [ 27 ]. Contrary to our results, two studies [ 38 , 39 ] found that the correlation has no statistically significant gender differences. These studies [ 38 , 39 ] used the open apices approach described by Cameriere et al [ 40 ], which is different from Demirjian et al's [ 41 ] method used in the present study.…”
Section: Discussioncontrasting
confidence: 99%